Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang Pasar Terapung di Kawasan Wisata Siring Tendean Kota Banjarmasin - Muksin, Ahmad; Rahmini, Noor (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to determine how factors influencing income such as business capital variables, education level, working hours, and business length affect the income of floating market traders in the Siring Tendean Tourism Area, Banjarmasin City. Data collection techniques using questionnaire techniques and interviews with a sample of respondents in the study totaling 40 respondents. The data analysis technique used is descriptive analysis with a quantitative approach that is the data presented in tabulations. The percentage of answers calculated from each of these categories is processed based on research needs and then presented according to findings in the field. The results showed that the variables of business capital, education level, working hours, and business length simultaneously had a significant effect on the income of the floating market traders in the Siring Tendean Tourism Area, Banjarmasin. The magnitude of the effect is 71.9%, and then the remaining 28.1% is explained by variables not mentioned in the study. From these results, working hours are the most dominant variable affecting the income of floating market traders in the Siring Tendean Tourism Area, Banjarmasin City